PERBANDINGAN HASIL BELAJAR MENGGUNAKAN MODEL DL DAN PjBL DENGAN MEMPERHATIKAN MINAT BELAJAR - Tri Yuli Susanti; Tedi Rusman; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2015)
This study examines the social studies learning outcomes comparison with Discovery Learning ( DL ) model and Project Based Learning (PjBL) by looking at the learning interest in class VIII SMP Negeri 1 Gadingrejo. The method used comparative with the experiment. The result of data analysis showed: (1) there is a difference of students average result study of social studies using DL models and PjBL models, (2) students result study by using DL are higher than PjBL for the students who have high interest in learning, (3) students result study by using DL are lower than PjBL for the students who have low interest in learning, (4) there is a difference of students average result study for the students who have high and low interest in learning, (5) there is an interaction between learning model and students interest to the students result study of social studies.Penelitian ini mengkaji tentang perbandingan hasil belajar IPS Terpadu dengan model Discovery Learning (DL) dan Project Based Learning (PjBL) dengan memperhatikan minat belajar kelas VIII SMP Negeri 1 Gadingrejo. Metode yang digunakan komparatif dengan pendekatan eksperimen. Hasil analisis (1) ada perbedaan rata-rata hasil belajar IPS Terpadu siswa yang pembelajarannya menggunakan model DL dan PjBL, (2) hasil belajar menggunakan model DL lebih tinggi dari pada model PjBL untuk siswa yang mempunyai minat belajar tinggi, (3) hasil belajar siswa menggunakan model DL lebih rendah dari pada model PjBL untuk siswa yang mempunyai minat belajar rendah, (4) ada perbedaan rata-rata hasil belajar siswa yang mempunyai minat tinggi dan rendah, (5) ada interaksi antara model pembelajaran dengan minat belajar siswa terhadap hasil belajar IPS Terpadu.Kata kunci :DL, hasil belajar, PjBL